Adventures of the undead at kinetochores - Sabine Elowe (Molecular & Cellular Oncology, 2021)
At the metaphase-to-anaphase transition, phosphatase activity feeds back to reverse early mitotic phosphorylation events. Our recent work indicates that the pseudokinase domain of the spindle checkpoint protein BUB1 (Budding Uninhibited by Benzimidazoles 1) mitotic checkpoint serine/threonine kinase B (BUB1B, BUBR1) maintains kinase–phosphatase balance at the outer kinetochore during mitotic exit.